Enhancing Historical Literacy and Critical Thinking through Primary Source-Based Inquiry: Evidence from the Jogja Library Center Tour - Kumalasari, Dyah; Gunartati, Gunartati; Wilis, Roro; Dewi, Ita Mutiara; Prayoga, Septian Yudi; Abdullah, Rabaah (Jurnal Pendidikan Progresif, 2025)
Enhancing Historical Literacy and Critical Thinking through Primary Source-Based Inquiry: Evidence from the Jogja Library Center Tour. Objectives: This study aims to analyze the implementation of the inquiry-based learning model “Yogyakarta Library Center Tour” in history learning. It utilizes old daily newspapers to improve historical literacy and its implications for developing critical thinking skills.  Methods: This study employed an explanatory sequential mixed-methods design, focusing on history learning at SMA Negeri 9 Yogyakarta, Indonesia. The location was chosen not only because of its success in realizing the School Literacy Movement through history learning, but also because of the uniqueness of the teachers' efforts in introducing the potential of the Jogja Library Centre as a repository of primary historical sources. Data collection techniques were comprehensively conducted through tests, interviews, observations, and document analysis. Sampling involved several subjects, including 28 students in quantitative analysis and seven key informants, including the Deputy Head of the Curriculum, history teachers, and student representatives from SMA Negeri 9 Yogyakarta, in qualitative analysis. Findings: The application of the inquiry model in history learning can represent historical literacy pedagogy by utilizing contemporary daily newspapers, such as Kedaulatan Rakyat, Kompas, Suara Karya, Suara Merdeka, Bernas, and Sinar Harapan, which were published during the New Order and Reformation eras as primary sources. Improvements in critical thinking skills were demonstrated through N-Gain analysis in several indicators, namely chronological thinking (0.57), historical understanding (0.52), historical evaluation and interpretation (0.50), and historical research skills (0.48). Conclusion: This study proposes a new approach to history learning by integrating tours to local archives and utilizing old newspapers as authentic primary sources. Its significance lies in its concrete contribution to strengthening source-based history learning and supporting the School Literacy Movement contextually. Keywords: jogja library center, historical literacy, inquiry model, critical thinking skill.